End‐of‐life care among adolescent and young adult patients with cancer living in poverty. Issue 4 (14th November 2019) - Roeland, Eric J.; Lindley, Lisa C.; Gilbertson‐White, Stephanie; Saeidzadeh, Seyedehtanaz; Currie, Erin R.; Friedman, Sarah; Bakitas, Marie; Mack, Jennifer W.
Abstract : Background: To the authors' knowledge, end‐of‐life (EOL) care outcomes among adolescents and young adults (AYAs) with cancer who are living in poverty remain poorly understood. The primary aim of the current study was to examine the effect of poverty on EOL care for AYA patients with cancer. Methods: The authors conducted a multisite, retrospective study of AYA patients with cancer aged 15 to 39 years who died between January 2013 and December 2016 at 3 academic sites. Medical record‐based EOL care outcomes included hospice referral, palliative care (PC) consultation, cancer treatment within the last month of life, and location of death. Two measures of poverty were applied: 1) zip code with a median income ≤200% of the federal poverty level; and 2) public insurance or lack of insurance. Logistic regression analyses were conducted. Results: A total of 252 AYA cancer decedents were identified. Approximately 41% lived in a high‐poverty zip code and 48% had public insurance or lacked insurance; approximately 70% had at least 1 poverty indicator. Nearly 40% had a hospice referral, 60% had a PC consultation (76% on an inpatient basis), 38% received EOL cancer treatment, and 39% died in the hospital. In bivariable analyses, AYA patients living in low‐income zip codes were found to be less likely to enroll in hospice ( P ≤ .01), have an early PC referral ( P ≤ .01), or receive EOL cancer treatment ( P = .03), although only EOL cancer treatment met statistical significance in multivariable models. No differences with regard to location of death ( P = .99) were observed. Conclusions: AYA patients with cancer experience low rates of hospice referral and high rates of in‐hospital death regardless of socioeconomic status. Future studies should evaluate early inpatient PC referrals as a possible method for improving EOL care. Abstract : Adolescent and young adult patients with cancer who live in poverty frequently experience inpatient death and chemotherapy near the end of life, raising concerns regarding the quality of end‐of‐life care. Early inpatient palliative care referrals may be one method with which to improve the end‐of‐life care of these patients, but this requires prospective validation.